Procesowy rachunek kosztów w zakładach opieki zdrowotnej - Jędrzejas, Bogusław (Course Costs Calculus in Health Care Institutions, 2008)
In conditions of the growing competition among health care institutions and more and more complex conditions of their functioning and financing, managers of these units require more detailed and multi complex economic information to take decisions. The basic source of calculus information is costs calculus where various analyses or institution budget can be constructed on its grounds. In the article, proposals of course cost calculus are introduced as one of the new instruments raising standard of given calculus information and improving management efficiency of health care institutions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 36, s. 143-153